Ebtanas SMUdan UMPTN Sebagai Bottleneck: Perlunya Pembaruan Kebijakan Penidikan yang Rasional - Yana Karyana (Magister Administrasi Publik, 2001)
As an instrument to gauge the competence and competition in learning process, Ebtanas (Standard National Grades) and UMPTN (Admission Test for State Universities) in Indonesian education system have changed into a myth of schooling. Not only that the Ebtanas and UMPTN have become the aims of schooling, but also become